Drone Testing and Education via Mixed Reality Simulation - Ren, Baoliang; Stewart, Nathan; Sanchez, Aria; Wang, Chuanrong (Journal of Computer Science and Software Applications, 2023)
With the rapid advancement of drone technology and computer graphics, the applications of drones and virtual reality devices are expanding. Consequently, there is an urgent need for drone developers to test drones quickly, affordably, and realistically. This paper proposes a drone simulation system designed within the HoloLens 2 mixed reality environment, enabling developers to conduct more realistic tests. Additionally, this system can be applied in the fields of drone education and gaming, providing a versatile tool for both development and instructional purposes.